Maternal Outcomes After Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in Vaccinated Compared With Unvaccinated Pregnant Patients. Issue 1 (January 2022) - Morgan, John A.; Biggio, Joseph R.; Martin, Jane K.; Mussarat, Naiha; Chawla, Harsheen K.; Puri, Priya; Williams, Frank B.
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination is associated with lower odds of severe or critical coronavirus disease 2019 (COVID-19) or COVID-19 of any severity in pregnant patients during the Delta-predominant fourth SARS-CoV-2 surge.